A museum studies approach to heritage - Watson, Sheila,Ed; Barnes, Amy,Ed; Bunning, Katy,Ed (Leicester readers in museum studies, 2019)
"Heritage's revival as a respected academic subject has, in part, resulted from an increased awareness and understanding of indigenous rights and non-Western philosophies and practices, and a growing respect for the intangible. Heritage has thus focused on management, tourism and the traditionally 'heritage-minded' disciplines, such as archaeology and geography, social and cultural theory. Scholarly work in this area has been in support of identity and community cohesion, as well as championing new approaches to ethics and values. Widening the scope of international heritage studies by drawing on a range of disciplines as well as the best from established sources, A Museum Studies Approach to Heritage explores heritage through new areas of knowledge including emotion and affect, the politics of dissent, migration and intercultural and participatory dimensions of heritage. It includes writing not typically recognised as 'heritage' but which, nevertheless, adds something significant to heritage debates: what heritage is, what it can do, how it works and for whom. The book includes heritage perspectives from beyond the professional sphere, serving as a reminder that heritage is not just the concern of the academic, but is a deeply felt and keenly valued public and private practice. This blending of traditional topics and emerging trends, established theory and concepts from other disciplines offers readers international views of the past and future of this growing field. A Museum Studies Approach to Heritage is an introductory reader for postgraduate students of heritage studies, museum studies and everyone interested in how we conceptualise and use the past"--